Half a century of the inverse care law: A comparison of general practitioner job satisfaction and patient satisfaction in deprived and affluent areas of Scotland. Issue 1 (February 2023) - Mercer, Stewart W; Lunan, Carey J; MacRae, Clare; Henderson, David AG; Fitzpatrick, Bridie; Gillies, John; Guthrie, Bruce; Reilly, Johanna
Background and Aims: The 'inverse care law', first described in 1971, results from a mismatch of healthcare need and healthcare supply in deprived areas. GPs in such areas struggle to cope with the high levels of demand resulting in shorter consultations and poorer patient outcomes. We compare recent national GP and patient satisfaction data to investigate the ongoing existence of this disparity in Scotland. Methods and Results: Secondary analysis of cross-sectional national surveys (2017/2018) on upper and lower deprivation quintiles. GP measures; job satisfaction, job stressors, positive and negative job attributes. Patient measures; percentage positive responses per practice on survey questions on access and consultation quality. GPs in high deprivation areas reported lower job satisfaction and positive job attributes, and higher job stressors and negative job attributes compared with GPs in low deprivation areas. Patients living in high deprivation areas reported lower satisfaction with access and consultation quality than patients in low deprivation areas. These differences in GP and patient satisfaction persisted after adjusting for confounding variables. Conclusions: Lower GP work satisfaction in deprived areas was mirrored by lower patient satisfaction. These findings add to the evidence that the inverse care law persists in Scotland, over 50 years after it was first described.